I2/TBHP-mediated oxidative coupling of ketones and toluene derivatives: a facile method for the preparation of α-benzoyloxy ketones. Issue 33 (7th April 2017) - Chen, Cui; Liu, Weibing; Zhou, Peng; Liu, Hailing
Abstract : Synthesis of α-benzoyloxy ketones from ketones and toluenes using TBHP as the surrogate of toxic heavy-metal oxidants and the oxygen source of the incorporated oxygen. Abstract : An efficient oxidative approach was developed for the α-benzoyloxylation of ketones using tert -butyl hydroperoxide (TBHP). This process provided facile access to a wide range of α-benzoyloxy ketones in good to excellent yields via the direct oxidative α-benzoyloxylation of a structurally diverse series of ketones using simple arylmethane compounds.